(3TQM OjHGLI GdTeSjIs - (3Ydj Hf YHO GdYRjR Hf MSGe Hf MGeO Hf Ce RGOg GdQhej,J (B980 (3g` s
(3ChdgG (B:s
(3EaJJM cJGHg HGdGSJYGQGJ GdOGdI Ydi Cf CMSf GdcdGe MeO eHOY Pi GdEfYGe s
(3BNQgG (B:s
(3hbOe GdeYehd ai hGddg CSCdg ddJNUjU , hjLfHfi Yf GdNWd , Ei GdNWC hGdEVWQGH hHjOg CReI GdJMbjb , LeY dReGe hGdMeO ddg Ydi GdJeGe JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdeJf HGdMeQI hGdTQM HGdShGOs
(3HChdgG bUjOI ddTjN TeS GdOjf GdbGOQi ai NeSI YTQ HjJkG HNW YHO GdQGRb Hf HcQi GdSeGfs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs